2020
DOI: 10.1590/s2175-97902019000418077
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional corticosteroid injection as an effective treatment method for oral lesions: a meta-analysis

Abstract: Intralesional corticosteroid injection (ICSI) is known as one of the main methods used for treating a wide range of lesions. It also results in a high concentration of drugs at lesion sites, with minimal systemic absorption. Thus, this study aimed to provide a review of the intralesional corticosteroid injection (ICSI) indications in the treatment of oral lesions. To this end; relevant key words were searched in the databases of PubMed, Google Scholar, Scopus, ScienceDirect, and UpToDate in the present study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
0
4
0
2
Order By: Relevance
“…However, complications associated with a single dose of corticosteroids are rare and have been reported in studies involving intralesional injection of corticosteroids. These include the complications such as pain, bleeding, and allergic reaction [ 38 ]. In the studies included in the analysis, none of them reported any significant complication which could be attributed to the single dose of corticosteroid.…”
Section: Discussionmentioning
confidence: 99%
“…However, complications associated with a single dose of corticosteroids are rare and have been reported in studies involving intralesional injection of corticosteroids. These include the complications such as pain, bleeding, and allergic reaction [ 38 ]. In the studies included in the analysis, none of them reported any significant complication which could be attributed to the single dose of corticosteroid.…”
Section: Discussionmentioning
confidence: 99%
“…16 Metanalisis yang dilakukan Gholizadeh et al terhadap penggunaan injeksi kortikosteroid intralesi pada lesi oral menyimpulkan bahwa pada kasus mukokel tampaknya kortikosteroid mengakibatkan akumulasi dan kontraksi perluasan saluran kelenjar saliva atau induksi pembekuan yang serupa dengan agen sklerosis. 17 Penggunaan agen sklerosis selain kortikosteroid telah dilaporkan oleh Gaikwad et al dengan agen terapi sodium tetradesil sulfat yang diencerkan dengan NaCl 0,9% dengan perbandingan 1:1. Mukokel sembuh sempurna setelah evaluasi 2 minggu pasca tindakan, meskipun pada 1 minggu sebelumnya tidak nampak pengurangan ukuran lesi.…”
Section: Pembahasanunclassified
“…61 Steroids have anti-inflammatory, antiproliferative, immunosuppressive, and vasoconstrictive properties which can help reduce pain and pruritus. 70,71 Steroids reduce collagen and glycosaminoglycan synthesis, inhibit fibroblast proliferation, and cause degeneration of collagen and fibroblasts. 3,72,73 Using intralesional corticosteroids allows for attainment of higher concentrations of steroid at the scar site with minimal systemic absorption.…”
Section: Injectable Therapiesmentioning
confidence: 99%
“…75 Typically, systemic side effects are not seen since low doses are used; however, it has been reported that repeated dosing with steroid injection can be associated with hypertension, heart failure, uncontrolled diabetes, and bacterial and fungal infections. 71 Intralesional injections have also been associated with early effects such as bleeding, bruising, infection, impaired wound healing, sterile abscesses, and delayed effects such as cutaneous and subcutaneous lipoatrophy, leukoderma, telangiectasia, and localized or distant steroid acne. 71,76 5-Fluorouracil (5FU) is a pyrimidine analog that inhibits thymidylate synthase enzyme.…”
Section: Injectable Therapiesmentioning
confidence: 99%
See 1 more Smart Citation